Pengaruh Current Ratio, Debt to Equty Ratio dan Total Assets Turnover terhadap Net Profit Margin pada Perusahaan Kosmetik di BEI Periode 2013-2017 - Sekar Marfita Stema (Universitas Batanghari Jambi, 2019)
The purpose of this reseach is to analyze the influence of Current Ratio (CR), Debt to Equity Ratio (DAR) and Total Assets Turnover (TATO) to Net Profit Margin(NPM) at Cosmetics Compaby in BEI Period 2013-2017. The research methodology used is descriptive method and statistical analysis method. Data type used in this research was conducted at Cosmetics Company during the period 2013-2017 using the Library Reseach data Collection method. Hypothesis testing is done by using F test dan t test, with significance level (α) 5%. Analyzing data using statistical data processing software that is SPSS 20.0 for windows. The result showed that the variable Current Ratio (CR), Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) simultaneously have a positive and significant effect on Net Profit Margin (NPM). Partially variable Current Ratio (CR) and Debt to Equity Ratio (DER) has no effect and not significant to Net Profit Margin . While Total Assets Turnover (TATO) has a positive and significant effect on Net Profit Margin (NPM) in cosmetics company. The results of this study is expected that the variable Total Assets Turnover (TATO) can be a guide, either by the management company in the management of the company, or by investors in determining investment strategy. Adjusted R2 test in this study amounted to 0,562. This shows that the Net Profit Margin is influenced by Current Ratio, Debt to Equity Ratio and Total Assets Turnover of 56,2%, while the remaining 43,8% is influenced by other variables not examined in this study. Keyword: CR, DER, TATO, and NPM